Biomechanical Profile after Dry Needling in Mixed Martial Arts - Trybulski, Robert; Kużdżał, Adrian; Stanula, Arkadiusz; Klich, Sebastian; Clemente, Filipe Manuel; Kawczyński, Adam; Fernández-de-las-Peñas, Cesar (International Journal of Sports Medicine, 2024)
The purpose of this study was to compare the effects of dry needling (DN) intervention on the responses of muscle tone, stiffness, and elasticity, as well as power, pressure pain thresholds, and blood perfusion of the flexor carpi radialis muscle in mixed martial arts (MMA) athletes. Thirty-two trained/developmental men MMA fighters (25.5±4.5 years; 24.5±3 body mass index) participated in a randomized crossover study. Participants underwent a single intervention, receiving both DN and placebo. Laser Doppler flowmetry measured blood perfusion, while a myotonometer assessed the mechanical characteristics of muscle tone, stiffness, and elasticity of the flexor carpi radialis muscle. Pressure pain thresholds (PPT) were measured using an algometer, and maximal forearm muscle force was measured using a hand dynamometer. Outcomes were assessed at baseline, immediately after, and 24 hours and 48 hours post-intervention. A two-way repeated-measures ANOVA revealed significant Intervention*Time interaction for all outcomes: perfusion unit (p<0.001), muscle tone (p<0.001), stiffness (p<0.001), elasticity (p<0.001), PPT (p<0.001) and maximal forearm muscle force (p<0.001). The current study suggests that a single session of DN enhances muscle recovery, increases muscle strength, and improved PPT in MMA athletes. These positive adaptations appear to last up to 48 hours in some variables.
Keywords: physical therapy modalities; therapeutics; muscle strength; sports medicine